Transforming growth factor beta signaling and craniofacial development: modeling human diseases in zebrafish - Fox, Sabrina C.; Waskiewicz, Andrew J. (Frontiers in Cell and Developmental Biology, 2024)
Humans and other jawed vertebrates rely heavily on their craniofacial skeleton for eating, breathing, and communicating. As such, it is vital that the elements of the craniofacial skeleton develop properly during embryogenesis to ensure a high quality of life and evolutionary fitness. Indeed, craniofacial abnormalities, including cleft palate and craniosynostosis, represent some of the most common congenital abnormalities in newborns. Like many other organ systems, the development of the craniofacial skeleton is complex, relying on specification and migration of the neural crest, patterning of the pharyngeal arches, and morphogenesis of each skeletal element into its final form. These processes must be carefully coordinated and integrated. One way this is achieved is through the spatial and temporal deployment of cell signaling pathways. Recent studies conducted using the zebrafish model underscore the importance of the Transforming Growth Factor Beta (TGF-) and Bone Morphogenetic Protein (BMP) pathways in craniofacial development. Although both pathways contain similar components, each pathway results in unique outcomes on a cellular level. In this review, we will cover studies conducted using zebrafish that show the necessity of these pathways in each stage of craniofacial development, starting with the induction of the neural crest, and ending with the morphogenesis of craniofacial elements. We will also cover human skeletal and craniofacial diseases and malformations caused by mutations in the components of these pathways (e.g., cleft palate, craniosynostosis, etc.) and the potential utility of zebrafish in studying the etiology of these diseases. We will also briefly cover the utility of the zebrafish model in joint development and biology and discuss the role of TGF-/BMP signaling in these processes and the diseases that result from aberrancies in these pathways, including osteoarthritis and multiple synostoses syndrome. Overall, this review will demonstrate the critical roles of TGF-/BMP signaling in craniofacial development and show the utility of the zebrafish model in development and disease.